Crisis Management in A Cultural Institution on The Example of a Selected Library During COVID 19 Pandemic - Marcin BERLIK; Agnieszka NAWROCKA (Communications of International Proceedings, 2021)
The aim of the article is to signal the problem of crisis management in cultural institutions. The authors point to the problem of insufficient anti-crisis measures or crisis management in cultural institutions, which results in their low resistance to crisis situations. Faced with the crisis caused by the COVID-19 pandemic, most institutions could only take passive actions in response to events, conditions that had already occurred. Using the example of the school library, the difficulties faced by cultural institutions during the pandemic and the fact that the state in which it found itself showed signs of crisis were pointed out. The publication discusses the most important management actions taken in response to the crisis.  However, they can only be classified as reactive crisis management activities aimed at reducing the severity of the negative impact of the pandemic on the entity’s objectives. This article characterizes the key treatments that have succeeded in rebuilding interest in reading and the best practices that can reinvigorate library work beyond the pandemic. It also indentified the reasons for the high vulnerability of cultural institutions to similar events and proposed actions that could increase to their resilience. The positive of crisis occurrence as an opportunity to develop and improve the organization’s work were also pointed out.
Keywords: crisis management; library; COVID; agile; resilence; cultural institution